Acute and subclinical Ehrlichia canis infection and cortisol response to ACTH stimulation test - Rondelli, Mariana Cristina H. [UNESP]; Munhoz, Thiago D.; Catandi, Pâmela B.; Freschi, Carla R. [UNESP]; Palacios Junior, Reinaldo J. G.; Machado, Rosângela Z. [UNESP]; Tinucci-Costa, Mirela [UNESP] (My University, 2015)
Adrenocortical disturbances are associated with canine ehrlichiosis due to the immunological changes caused by infection and consequent inflammation. Thus, this study aimed to evaluate the occurrence of adrenocortical hormonal changes in dogs naturally infected with Ehrlichia canis (n=21) as confirmed by the presence of anti-E. canis antibodies (Dot-ELISA) and nested PCR (nPCR). Serum cortisol concentrations were assessed by radioimmunoassay before and one hour after ACTH stimulation. Ten healthy dogs were subjected to the same stimulation protocol and used as controls. The results revealed that the dogs with naturally acquired acute and subclinical ehrlichiosis secreted cortisol following ACTH stimulation in similar concentrations to those of healthy dogs.
Keywords: Adrenal; Canine ehrlichiosis; Dogs; Hormones